Potential protection of computer gaming against mental health issues: Evidence from a Mendelian randomization study. (July 2023) - Li, Hansen; Zhang, Xing; Cao, Yang; Zhang, Guodong
Abstract: Computer gaming may negatively impact mental health. To mitigate the inherent defects of the existing observational studies, we employed the Mendelian randomization (MR) design to examine the role of computer gaming on mental health issues using large-scale genome-wide association study (GWAS) data. A computer gaming and four mental health issue datasets were obtained from UK-Biobank and FinnGen respectively. We evaluated the causal effects using inverse variance weighted (IVW), weighted median, and MR-Egger estimators, followed by a series of sensitivity analyses. We found no distinctive results under a Bonferroni-corrected significance level ( p < 0.013). Nevertheless, we observed suggestive evidence in IVW estimations supporting the causal effects of computer gaming on depression medication consumption (OR = 0.579; 95%CI: 0.347–0.996; p = 0.036) and anxiety disorders (OR = 0.471; 95%CI: 0.246–0.903, p = 0.023). Our findings indicate a potential protective effect of computer gaming against mental health issues, which underscores the bright sides of computer gaming, and also offers insights into the health promotion strategies based on digital interventions. Given our limitations, we call for future research to re-examine our findings and explore underlying mechanisms. Highlights: The mental health impacts of computer gaming were assessed by the Mendelian randomization approach. The frequency of computer gaming may reduce depression medication consumption. The frequency of computer gaming may reduce anxiety disorders. Future research is warranted to explore the role of stress in these associations.